# 积分表

## 含有${\displaystyle ax+b}$的积分

${\displaystyle \int \ (ax+b)^{n}{\mbox{d}}x={\frac {(ax+b)^{n+1}}{a(n+1)}}+C}$
${\displaystyle \int {\frac {1}{ax+b}}{\mbox{d}}x={\frac {1}{a}}\ln \left|ax+b\right|+C}$
${\displaystyle \int {\frac {x}{ax+b}}{\mbox{d}}x={\frac {1}{a^{2}}}(ax+b-b\ln \left|ax+b\right|)+C}$
${\displaystyle \int {\frac {x^{2}}{ax+b}}{\mbox{d}}x={\frac {1}{2a^{3}}}\left[(ax+b)^{2}-4b(ax+b)+2b^{2}\ln \left|ax+b\right|\right]+C}$
${\displaystyle \int {\frac {1}{x(ax+b)}}{\mbox{d}}x=-{\frac {1}{b}}\ln \left|{\frac {ax+b}{x}}\right|+C}$
${\displaystyle \int {\frac {1}{x^{2}(ax+b)}}{\mbox{d}}x={\frac {a}{b^{2}}}\ln \left|{\frac {ax+b}{x}}\right|-{\frac {1}{bx}}+C}$

## 含有${\displaystyle {\sqrt {a+bx}}}$的积分

${\displaystyle \int x{\sqrt {a+bx}}{\mbox{d}}x={\frac {2}{15b^{2}}}(3bx-2a)(a+bx)^{\frac {3}{2}}+C}$
${\displaystyle \int x^{2}{\sqrt {a+bx}}{\mbox{d}}x={\frac {2}{105b^{3}}}(15b^{2}x^{2}-12abx+8a^{2})(a+bx)^{\frac {3}{2}}+C}$
${\displaystyle \int x^{n}{\sqrt {a+bx}}{\mbox{d}}x={\frac {2}{b(2n+3)}}x^{n}(a+bx)^{\frac {3}{2}}-{\frac {2na}{b(2n+3)}}\int x^{n-1}{\sqrt {a+bx}}{\mbox{d}}x}$
${\displaystyle \int {\frac {\sqrt {a+bx}}{x}}{\mbox{d}}x=2{\sqrt {a+bx}}+a\int {\frac {1}{x{\sqrt {a+bx}}}}{\mbox{d}}x}$
${\displaystyle \int {\frac {\sqrt {a+bx}}{x^{n}}}{\mbox{d}}x={\frac {-1}{a(n-1)}}{\frac {(a+bx)^{\frac {3}{2}}}{x^{n-1}}}-{\frac {(2n-5)b}{2a(n-1)}}\int {\frac {\sqrt {a+bx}}{x^{n-1}}}{\mbox{d}}x,n\neq 1}$
${\displaystyle \int {\frac {1}{x{\sqrt {a+bx}}}}{\mbox{d}}x={\frac {1}{\sqrt {a}}}\ln \left({\frac {{\sqrt {a+bx}}-{\sqrt {a}}}{{\sqrt {a+bx}}+{\sqrt {a}}}}\right)+C,a>0}$
${\displaystyle ={\frac {2}{\sqrt {-a}}}\arctan {\sqrt {\frac {a+bx}{-a}}}+C,a<0}$
${\displaystyle \int {\frac {x}{\sqrt {a+bx}}}{\mbox{d}}x={\frac {2(a+bx)^{\frac {3}{2}}}{3b^{2}}}-{\frac {(2a){\sqrt {a+bx}}}{b^{2}}}}$
${\displaystyle \int {\frac {1}{x^{n}{\sqrt {a+bx}}}}{\mbox{d}}x={\frac {-1}{a(n-1)}}{\frac {\sqrt {a+bx}}{x^{n-1}}}-{\frac {(2n-3)b}{2a(n-1)}}\int {\frac {1}{x^{n-1}}}{\sqrt {a+bx}}{\mbox{d}}x,n\neq 1}$

## 含有${\displaystyle x^{2}\pm \alpha ^{2}}$的积分

${\displaystyle \int {\frac {1}{x^{2}+\alpha ^{2}}}{\mbox{d}}x={\frac {\arctan {\dfrac {x}{\alpha }}}{\alpha }}+C}$
${\displaystyle \int {\frac {1}{\pm x^{2}\mp \alpha ^{2}}}{\mbox{d}}x={\frac {\ln \left({\dfrac {x\mp \alpha }{\pm x+\alpha }}\right)}{2\alpha }}+C}$

## 含有 ${\displaystyle {ax^{2}+b}}$的积分

${\displaystyle \int {\frac {1}{ax^{2}+b}}{\mbox{d}}x={\frac {1}{\sqrt {ab}}}\arctan {\frac {{\sqrt {a}}x}{\sqrt {b}}}+C}$

## 含有 ${\displaystyle ax^{2}+bx+c}$的积分

${\displaystyle \int ax^{2}+bx+c{\mbox{d}}x={\frac {ax^{3}}{3}}+{\frac {bx^{2}}{2}}+cx+C}$

## 含有 ${\displaystyle {\sqrt {a^{2}+x^{2}}}\qquad (a>0)}$的积分

${\displaystyle \int {\sqrt {a^{2}+x^{2}}}{\mbox{d}}x={\frac {1}{2}}x{\sqrt {a^{2}+x^{2}}}+{\frac {1}{2}}a^{2}\ln \left(x+{\sqrt {a^{2}+x^{2}}}\right)+C}$
${\displaystyle \int x^{2}{\sqrt {a^{2}+x^{2}}}{\mbox{d}}x={\frac {1}{8}}x(a^{2}+2x^{2}){\sqrt {a^{2}+x^{2}}}-{\frac {1}{8}}a^{4}\ln \left(x+{\sqrt {a^{2}+x^{2}}}\right)+C}$
${\displaystyle \int {\frac {\sqrt {a^{2}+x^{2}}}{x}}{\mbox{d}}x={\sqrt {a^{2}+x^{2}}}-a\ln \left({\frac {a+{\sqrt {a^{2}+x^{2}}}}{x}}\right)+C}$
${\displaystyle \int {\frac {\sqrt {a^{2}+x^{2}}}{x^{2}}}{\mbox{d}}x=\ln \left(x+{\sqrt {a^{2}+x^{2}}}\right)-{\frac {\sqrt {a^{2}+x^{2}}}{x}}+C}$
${\displaystyle \int {\frac {1}{\sqrt {a^{2}+x^{2}}}}{\mbox{d}}x=\ln \left(x+{\sqrt {a^{2}+x^{2}}}\right)+C}$
${\displaystyle \int {\frac {x^{2}}{\sqrt {a^{2}+x^{2}}}}{\mbox{d}}x={\frac {1}{2}}x{\sqrt {a^{2}+x^{2}}}-{\frac {1}{2}}a^{2}\ln \left({\sqrt {a^{2}+x^{2}}}+x\right)+C}$
${\displaystyle \int {\frac {1}{x{\sqrt {a^{2}+x^{2}}}}}{\mbox{d}}x={\frac {1}{a}}\ln \left({\frac {x}{a+{\sqrt {a^{2}+x^{2}}}}}\right)+C}$
${\displaystyle \int {\frac {1}{x^{2}{\sqrt {a^{2}+x^{2}}}}}{\mbox{d}}x=-{\frac {\sqrt {a^{2}+x^{2}}}{a^{2}x}}+C}$

## 含有${\displaystyle {\sqrt {x^{2}-a^{2}}}\qquad {(x^{2}>a^{2})}}$的积分

${\displaystyle \int {\frac {1}{\sqrt {x^{2}-a^{2}}}}{\mbox{d}}x=\ln |x+{\sqrt {x^{2}-a^{2}}}|+C}$

## 含有${\displaystyle {\sqrt {a^{2}-x^{2}}}\qquad (a^{2}>x^{2})}$的积分

${\displaystyle \int {\sqrt {a^{2}-x^{2}}}{\mbox{d}}x={\frac {1}{2}}x{\sqrt {a^{2}-x^{2}}}+{\frac {a^{2}}{2}}\arcsin {\frac {x}{a}}+C}$
${\displaystyle \int {\frac {1}{\sqrt {a^{2}-x^{2}}}}{\mbox{d}}x=\arcsin {\frac {x}{a}}+C=-\arccos {\frac {x}{a}}+C}$
${\displaystyle \int x^{2}{\sqrt {a^{2}-x^{2}}}{\mbox{d}}x={\frac {1}{8}}x(2x^{2}-a^{2}){\sqrt {a^{2}-x^{2}}}+{\frac {1}{8}}a^{4}\arcsin {\frac {x}{a}}+C}$
${\displaystyle \int {\frac {\sqrt {a^{2}-x^{2}}}{x}}{\mbox{d}}x={\sqrt {a^{2}-x^{2}}}-a\ln \left({\frac {a+{\sqrt {a^{2}-x^{2}}}}{x}}\right)+C}$
${\displaystyle \int {\frac {\sqrt {a^{2}-x^{2}}}{x^{2}}}{\mbox{d}}x=-{\frac {\sqrt {a^{2}-x^{2}}}{x}}-\arcsin {\frac {x}{a}}+C}$
${\displaystyle \int {\frac {1}{x{\sqrt {a^{2}-x^{2}}}}}{\mbox{d}}x=-{\frac {1}{a}}\ln \left({\frac {a+{\sqrt {a^{2}-x^{2}}}}{x}}\right)+C}$
${\displaystyle \int {\frac {x^{2}}{\sqrt {a^{2}-x^{2}}}}{\mbox{d}}x=-{\frac {1}{2}}x{\sqrt {a^{2}-x^{2}}}+{\frac {1}{2}}a^{2}\arcsin {\frac {x}{a}}+C}$
${\displaystyle \int {\frac {1}{x^{2}{\sqrt {a^{2}-x^{2}}}}}{\mbox{d}}x=-{\frac {\sqrt {a^{2}-x^{2}}}{a^{2}x}}+C}$

## 含有${\displaystyle R={\sqrt {|a|x^{2}+bx+c}}\qquad (a\neq 0)}$的积分

${\displaystyle \int {\frac {{\mbox{d}}x}{R}}={\frac {1}{\sqrt {a}}}\ln \left(2{\sqrt {a}}R+2ax+b\right)\qquad ({\mbox{for }}a>0)}$
${\displaystyle \int {\frac {{\mbox{d}}x}{R}}={\frac {1}{\sqrt {a}}}\,\operatorname {arsinh} {\frac {2ax+b}{\sqrt {4ac-b^{2}}}}\qquad {\mbox{(for }}a>0{\mbox{, }}4ac-b^{2}>0{\mbox{)}}}$
${\displaystyle \int {\frac {{\mbox{d}}x}{R}}={\frac {1}{\sqrt {a}}}\ln |2ax+b|\quad {\mbox{(for }}a>0{\mbox{, }}4ac-b^{2}=0{\mbox{)}}}$
${\displaystyle \int {\frac {{\mbox{d}}x}{R}}=-{\frac {1}{\sqrt {-a}}}\arcsin {\frac {2ax+b}{\sqrt {b^{2}-4ac}}}\qquad {\mbox{(for }}a<0{\mbox{, }}4ac-b^{2}<0{\mbox{, }}\left(2ax+b\right)<{\sqrt {b^{2}-4ac}}{\mbox{)}}}$
${\displaystyle \int {\frac {{\mbox{d}}x}{R^{3}}}={\frac {4ax+2b}{(4ac-b^{2})R}}}$
${\displaystyle \int {\frac {{\mbox{d}}x}{R^{5}}}={\frac {4ax+2b}{3(4ac-b^{2})R}}\left({\frac {1}{R^{2}}}+{\frac {8a}{4ac-b^{2}}}\right)}$
${\displaystyle \int {\frac {{\mbox{d}}x}{R^{2n+1}}}={\frac {2}{(2n-1)(4ac-b^{2})}}\left[{\frac {2ax+b}{R^{2n-1}}}+4a(n-1)\int {\frac {{\mbox{d}}x}{R^{2n-1}}}\right]}$
${\displaystyle \int {\frac {x}{R}}\;{\mbox{d}}x={\frac {R}{a}}-{\frac {b}{2a}}\int {\frac {{\mbox{d}}x}{R}}}$
${\displaystyle \int {\frac {x}{R^{3}}}\;{\mbox{d}}x=-{\frac {2bx+4c}{(4ac-b^{2})R}}}$
${\displaystyle \int {\frac {x}{R^{2n+1}}}\;{\mbox{d}}x=-{\frac {1}{(2n-1)aR^{2n-1}}}-{\frac {b}{2a}}\int {\frac {{\mbox{d}}x}{R^{2n+1}}}}$
${\displaystyle \int {\frac {{\mbox{d}}x}{xR}}=-{\frac {1}{\sqrt {c}}}\ln \left({\frac {2{\sqrt {c}}R+bx+2c}{x}}\right)}$
${\displaystyle \int {\frac {{\mbox{d}}x}{xR}}=-{\frac {1}{\sqrt {c}}}\operatorname {arsinh} \left({\frac {bx+2c}{|x|{\sqrt {4ac-b^{2}}}}}\right)}$

## 含有三角函数的积分

${\displaystyle \int \cos x{\mbox{d}}x=\sin x+C}$
${\displaystyle \int \sin x{\mbox{d}}x=-\cos x+C}$
${\displaystyle \int \sec ^{2}x{\mbox{d}}x=\tan x+C}$
${\displaystyle \int \csc ^{2}x{\mbox{d}}x=-\cot x+C}$
${\displaystyle \int \sec x\tan x{\mbox{d}}x=\sec x+C}$
${\displaystyle \int \csc x\cot x{\mbox{d}}x=-\csc x+C}$
${\displaystyle \int \tan x{\mbox{d}}x=-\ln {\left|\cos {x}\right|}+C=\ln {\left|\sec x\right|}+C}$
${\displaystyle \int \cot x{\mbox{d}}x=\ln {\left|\sin x\right|}+C}$
${\displaystyle \int \sec x{\mbox{d}}x=\ln {\left|\sec x+\tan x\right|}+C}$
${\displaystyle \int \csc x{\mbox{d}}x=\ln {\left|\csc x-\cot x\right|}+C=\ln {\left|{\tan x-\sin x \over \sin x\tan x}\right|}+C}$

${\displaystyle \int \sin ^{n}x{\mbox{d}}x=-{\frac {1}{n}}\sin ^{n-1}x\cos x+{\frac {n-1}{n}}\int \sin ^{n-2}x{\mbox{d}}x+C\quad \forall n\geq 2}$
${\displaystyle \int \sin ^{2}x{\mbox{d}}x={\frac {x}{2}}-{\frac {\sin {2x}}{4}}+C}$

${\displaystyle \int \cos ^{n}x{\mbox{d}}x={\frac {1}{n}}\cos ^{n-1}x\sin x+{\frac {n-1}{n}}\int \cos ^{n-2}x{\mbox{d}}x+C\quad \forall n\geq 2}$
${\displaystyle \int \cos ^{2}x{\mbox{d}}x={\frac {x}{2}}+{\frac {\sin {2x}}{4}}+C}$

${\displaystyle \int \tan ^{n}x{\mbox{d}}x={\frac {1}{n-1}}\tan ^{n-1}x-\int \tan ^{n-2}x{\mbox{d}}x+C\quad \forall n\geq 2}$
${\displaystyle \int \tan ^{2}x{\mbox{d}}x=\tan x-x+C}$

${\displaystyle \int \cot ^{n}x{\mbox{d}}x=-{\frac {1}{n-1}}\cot ^{n-1}x-\int \cot ^{n-2}x{\mbox{d}}x+C\quad \forall n\geq 2}$
${\displaystyle \int \cot ^{2}x{\mbox{d}}x=-\cot x-x+C}$

${\displaystyle \int \sec ^{n}x{\mbox{d}}x={\frac {1}{n-1}}\sec ^{n-2}x\tan x+{\frac {n-2}{n-1}}\int \sec ^{n-2}x{\mbox{d}}x+C\quad \forall n\geq 2}$

${\displaystyle \int \csc ^{n}x{\mbox{d}}x=-{\frac {1}{n-1}}\csc ^{n-2}x\cot x+{\frac {n-2}{n-1}}\int \csc ^{n-2}x{\mbox{d}}x+C\quad \forall n\geq 2}$

## 含有反三角函数的积分

${\displaystyle \int \arcsin x{\mbox{d}}x=x\arcsin x+{\sqrt {1-x^{2}}}+C}$
${\displaystyle \int \arccos x{\mbox{d}}x=x\arccos x-{\sqrt {1-x^{2}}}+C}$
${\displaystyle \int \arctan {x}\,dx=x\arctan {x}-{\frac {1}{2}}\ln {\vert 1+x^{2}\vert }+C}$
${\displaystyle \int \operatorname {arccot} {x}\,dx=x\operatorname {arccot} {x}+{\frac {1}{2}}\ln {\vert 1+x^{2}\vert }+C}$
${\displaystyle \int \operatorname {arcsec} x{\mbox{d}}x=x\operatorname {arcsec} x-\operatorname {sgn}(x)\ln \left|x+{\sqrt {x^{2}-1}}\right|+C=x\operatorname {arcsec} x+\operatorname {sgn}(x)\ln \left|x-{\sqrt {x^{2}-1}}\right|+C}$
${\displaystyle \int \operatorname {arccsc} x{\mbox{d}}x=x\operatorname {arccsc} x+\operatorname {sgn}(x)\ln \left|x+{\sqrt {x^{2}-1}}\right|+C=x\operatorname {arccsc} x-\operatorname {sgn}(x)\ln \left|x-{\sqrt {x^{2}-1}}\right|+C}$

## 含有指数函数的积分

${\displaystyle \int e^{x}{\mbox{d}}x=e^{x}+C}$
${\displaystyle \int \alpha ^{x}{\mbox{d}}x={\frac {\alpha ^{x}}{\ln \alpha }}+C}$
${\displaystyle \int xe^{ax}{\mbox{d}}x={\frac {1}{a^{2}}}(ax-1)e^{ax}+C}$
${\displaystyle \int x^{n}e^{ax}{\mbox{d}}x={\frac {1}{a}}x^{n}e^{ax}-{\frac {n}{a}}\int x^{n-1}e^{ax}{\mbox{d}}x}$
${\displaystyle \int e^{ax}\sin bx{\mbox{d}}x={\frac {e^{ax}}{a^{2}+b^{2}}}(a\sin bx-b\cos bx)+C}$
${\displaystyle \int e^{ax}\cos bx{\mbox{d}}x={\frac {e^{ax}}{a^{2}+b^{2}}}(a\cos bx+b\sin bx)+C}$

## 含有对数函数的积分

${\displaystyle \int \ln x{\mbox{d}}x=x\ln x-x+C}$
${\displaystyle \int \log _{\alpha }x{\mbox{d}}x={\frac {1}{\ln \alpha }}\left({x\ln x-x}\right)+C}$
${\displaystyle \int x^{n}\ln x{\mbox{d}}x={\frac {x^{n+1}}{(n+1)^{2}}}[(n+1)\ln x-1]+C}$
${\displaystyle \int {\frac {1}{x\ln {x}}}{\mbox{d}}x=\ln {(\ln {x})}+C}$

## 含有双曲函数的积分

${\displaystyle \int \sinh x{\mbox{d}}x=\cosh x+C}$
${\displaystyle \int \cosh x{\mbox{d}}x=\sinh x+C}$
${\displaystyle \int \tanh x{\mbox{d}}x=\ln \left(\cosh x\right)+C}$
${\displaystyle \int \coth x{\mbox{d}}x=\ln \left|\sinh x\right|+C}$
${\displaystyle \int {\mbox{sech}}\ x{\mbox{d}}x=\arcsin \left(\tanh x\right)+C=\arctan \left(\sinh x\right)+C}$
${\displaystyle \int {\mbox{csch}}\ x{\mbox{d}}x=\ln \left|\tanh {x \over 2}\right|+C}$

## 定积分

${\displaystyle \int _{-\infty }^{\infty }e^{-\alpha x^{2}}{\mbox{d}}x={\sqrt {\frac {\pi }{\alpha }}}}$
${\displaystyle \int _{0}^{\frac {\pi }{2}}{\mbox{sin}}^{n}x{\mbox{d}}x=\int _{0}^{\frac {\pi }{2}}{\mbox{cos}}^{n}x{\mbox{d}}x={\begin{cases}{\frac {n-1}{n}}\cdot {\frac {n-3}{n-2}}\cdot \ldots \cdot {\frac {4}{5}}\cdot {\frac {2}{3}},&{\mbox{if }}n>1{\mbox{ 且 }}n{\mbox{為 奇 數 }}\\{\frac {n-1}{n}}\cdot {\frac {n-3}{n-2}}\cdot \ldots \cdot {\frac {3}{4}}\cdot {\frac {1}{2}}\cdot {\frac {\pi }{2}},&{\mbox{if }}n>0{\mbox{ 且 }}n{\mbox{為 偶 數 }}\end{cases}}}$